CORRECTION OF SIGNS OF ASTHENO-VEGETATIVE SYNDROME, PSYCHO-EMOTIONAL STATE AND SLEEP QUALITY BY MEANS OF PHYSICAL THERAPY IN MILITARY PERSONNEL WITH CONSEQUENCES OF TRAUMATIC BRAIN INJURY AND COMPLICATED BRUXISM - Kovalets, R. I.; Aravitska, M. G.; Ilnytskyi, N. R. (Rehabilitation and Recreation, 2025)
Objective. The aim of the study was to assess the effectiveness of the developed physical therapy program in military personnel with the consequences of closed traumatic brain injury and complicated bruxism, by analyzing the dynamics of astheno-vegetative syndrome, psycho-emotional state (anxiety, depression), sleep quality and multidimensional fatigue.Material. 98 men participated in the prospective study. The control group (CtrlG, n=35) consisted of men without dental lesions and TBI (mean age 29.3±1.7 years). The comparison group (n=32) consisted of civilians with bruxism in combination with temporomandibular joint dysfunction, who received only the wearing of individual relaxing occlusal splints. The main group (МG, n=31) consisted of military personnel aged 30.6±1.8 years with the consequences of traumatic brain injury and complicated bruxism, who underwent a physical therapy program in combination with wearing occlusal splints (duration 2 months – 14 inpatient sessions, 14 telerehabilitation sessions, 14 sessions of independent exercises). All participants were assessed at the beginning of the study: Hospital Anxiety and Depression Scale (HADS), Pittsburgh Sleep Quality Index (PSQI), Multidimensional Fatigue Inventory (MFI 20), autonomic nervous system function – according to 24-hour monitoring of heart rate variability.Results. In the control group, low mass indices of anxiety (4 [3; 4]) and depression (3 [2; 3]), PSQI 5.16±0.36, moderate level of fatigue (MFI 20: general fatigue 8 [5; 11]) were recorded. In the comparison group, a significant increase in anxiety to 8 [7; 9] (100% relative to the CtrlG) and depression to 9 [8; 10] (200%), PSQI=12.17±1.03 (136%), multidimensional fatigue was also higher: general fatigue 10 [7; 12] (25%). In the МG before physical therapy, the level of anxiety was 12 [10; 14] (200% of the CtrlG), depression 11 [10; 13] (267%), PSQI=18.37±1.15 (256%), general fatigue 16 [13; 18] (100% of the CtrlG). After physical therapy, in the МG, anxiety decreased to 7 [6; 8] (41.7%), depression to 6 [6; 7] (45.5%), PSQI to 10.58±0.62 (42.4%), general fatigue to 11 [9; 13] (31.3%), physical fatigue to 12 [9; 15] (20%). Autonomic function indicators also improved: LF decreased from 2809.31±51.40 to 2067.92±42.19 ms² (26.4%), HF increased from 712.19±15.28 to 831.26±17.12 ms² (16.7%), LF/HF ratio decreased from 3.94±0.19 to 2.49±0.09 (36.8%), Baevsky index decreased from 230.19±14.65 to 173.22±15.45 points (4.7%). Conclusions. In military personnel with traumatic brain injury and complicated bruxism, disorders of autonomic regulation, psychoemotional state, sleep, and increased fatigue were found. It has been shown that a comprehensive physical therapy program in combination with occlusal treatment provides a statistically significant improvement in all measured parameters (p<0.05).